The novel mef(C)–mph(G) macrolide resistance genes are conveyed in the environment on various vectors. (September 2017) - Sugimoto, Yuta; Suzuki, Satoru; Nonaka, Lisa; Boonla, Chanchai; Sukpanyatham, Nop; Chou, Hsin-Yiu; Wu, Jer-Horng
Highlights: Macrolide resistance genes mef (C)– mph (G) were found in Japan, Taiwan and Thailand. Different types of mobile genetic elements were found to carry mef (C)– mph (G). mef (C)– mph (G) in isolates from different environment showed the same sequence. Abstract: Background: The novel tandem genes mef (C) and mph (G) have been reported in marine bacteria in Japan. This paper aimed to characterise the extent of environmental distribution of mef (C) and mph (G) as well as their dissemination and persistence in aquatic bacterial communities. Methods: Erythromycin-resistant bacteria were isolated from Japan, Taiwan and Thailand aquaculture sites. The mef (C)– mph (G) genes were detected by PCR. The size of mobile genetic elements conveying mef (C) and mph (G) was examined by Southern blotting. The conjugation rate was assessed by filter mating. Results: The mef (C)– mph (G) tandem genes were distributed in erythromycin-resistant isolates from aquaculture seawater in Japan and northern Taiwan and in animal farm wastewater in Thailand. A total of 29 bacterial isolates were positive for mef (C)– mph (G). The genes were found on vectors of various sizes. Partial sequencing of the traI relaxase gene revealed homology with a pAQU1-like plasmid, an IncA/C-type plasmid and an SXT/R391 family integrative conjugative element (SRI) as vectors. Thirteen isolates (45%) were positive for traI (pAQU-IncA/C-SRI), whereas the others were negative. The traI (pAQU-IncA/C-SRI)-positive isolates exhibited a higher transfer frequency (10 −4 –10 −5 transconjugants/donor) than traI (pAQU-IncA/C-SRI)-negative isolates (<10 −9 ). Conclusions: These results suggest that mef (C)– mph (G) are coded on various vectors and are distributed among marine and wastewater bacteria in Asian countries. Vectors with traI (pAQU-IncA/C-SRI) play a role in the spread of mef (C)– mph (G).